Evaluation of mouse urinary bladder smooth muscle for diurnal differences in contractile properties - White, Rachel S.; Zemen, Betsir G.; Khan, Zulqarnain; Montgomery, Jenna R.; Herrera, Gerald M.; Meredith, Andrea L. (Frontiers in Pharmacology, 2015)
Most physiological systems show daily variations in functional output, entrained to the day-night cycle. Humans exhibit a daily rhythm in urinary voiding (micturition), and disruption of this rhythm (nocturia) has significant clinical impact. However, the underlying mechanisms are not well-understood. Recently, a circadian rhythm in micturition was demonstrated in rodents, correlated with functional changes in urodynamics, providing the opportunity to address this issue in an animal model. Smooth muscle cells from mouse bladder have been proposed to express a functional and autonomous circadian clock at the molecular level. In this study, we addressed whether a semi-intact preparation of mouse urinary bladder smooth muscle (UBSM) exhibited measurable differences in contractility between day and night. UBSM tissue strips were harvested at 4 time points over the diurnal cycle, and spontaneous (phasic) and nerve-evoked contractions were assessed using isometric tension recordings. During the active period (ZT12-24) when micturition frequency is higher in rodents, UBSM strips had no significant differences in maximal- (high K+) or nerve-evoked contractions compared to strips harvested from the resting period (ZT0-12). However, a diurnal rhythm in phasic contraction was observed, with higher amplitudes at ZT10. Consistent with the enhanced phasic amplitudes, expression of the BK K+ channel, a key suppressor of UBSM excitability, was lower at ZT8. Higher expression of BK at ZT20 was correlated with an enhanced effect of the BK antagonist paxilline on phasic amplitude, but paxilline had no significant time-of-day dependent effect on phasic frequency or nerve-evoked contractions. Overall, these results identify a diurnal difference for one contractile parameter of bladder muscle. Taken together, the results suggest that autonomous clocks in UBSM make only a limited contribution to the integrated control of diurnal micturition patterns.